(untitled) (Ozone Therapy Global Journal, 2019)
VI Congreso de la Sociedad Mexicana de Ozono TerapiaVI Congress of Mexican Ozone Therapy Association (AMOZON) Cancún, México, 17- 19 noviembre 2018. “Empoderando la Ozono Terapia en la Ciencia y El Servicio””Supporting the Scientific Bases and Applicability of Ozone Therapy” Abstract Book / Resúmenes